“Not a Woman-Hater,” “No Rapist,” or Even Inventor of “the Sensitive Male”? Feminist Interpretations of Hobbes’s Political Theory and Their Relevance for Hobbes Studies - Odzuck, Eva (Interpreting Hobbes's Political Philosophy, 2019)
The article discusses Hobbes’s role as a figure within feminist theory, the presence of gender-related topics in contemporary Hobbes studies, and options for fruitful collaboration between Hobbes studies and feminist theory. The article is divided in two major sections and a conclusion. A first section is devoted to demarcating the richness and inherent diversity of feminist interpretations of Hobbes and to showing that feminist questions and perspectives can be of great systematic relevance for understanding the foundations of Hobbes’s political philosophy. The second section shows how topics from feminist theory and gender-related questions have been addressed in Hobbes scholarship to date and discusses three selected examples of the last decade that indicate the extent to which the feminist challenge has been addressed by Hobbes scholarship. In a short conclusion and summary, the article identifies opportunities for fruitful collaboration between feminist theorists and Hobbes scholars as well as related topics of systematic relevance for Hobbes studie
CRIS-Team WoS Importer:2021-10-18
Keywords: Hobbes; Political Theory; gender; feminism; feminist political theory; contract; power; consent; nature.